Peningkatan Kompetensi Guru STEM Dalam Pembelajaran Informatika Berbasis HOTS dan Computational Thinking Guna Mendukung Implementasi Kurikulum Merdeka di MTsN I Mataram - Dyah Susilowati; Reny Refitaningsih Peby Ria; Rini Anggriani; Suci Indah Salsabila; Rifqi Aditia; Fatahul Aziz (Journal of Community Development, 2025)
Increasing teacher competence in learning informatics based on Higher Order Thinking Skills (HOTS) and Computational Thinking in the Merdeka Curriculum is an important aspect in facing educational challenges in the digital era. The importance of increasing teacher competence in HOTS and Computational Thinking-based informatics learning lies in the ability to equip students with critical and analytical skills needed in the digital era. In addition, competent teachers can create an innovative learning environment, so that students are better able to face complex challenges in the future and are ready to contribute optimally in society. Therefore, the objectives of this service activity are 1) conducting training for STEM teachers (Informatics, Science, Mathematics subjects) in implementing Informatics learning. (2) Training in compiling HOTS and Computational Thinking based learning assessments, (3) Training in laboratory management.. This activity was attended by 20 teachers, laboratory managers at MTsN 1 Mataram. The results of this activity are proven: (1) STEM teacher competency training in Informatics learning, the average pre-test is 39% and post-test is 96% there is an increase of 58%. (2) HOTS and Computational Thinking assessment preparation training, the average pre-test is 60% and post-test is 94% there is an increase of 34%. (3) Laboratory management training, the average pre-test is 48% and post-test is 89% there is an increase of 41%. Thus, this activity has succeeded in improving teacher skills in utilizing information technology and applying it to the preparation of assessments in learning while improving the overall management capabilities of laboratory management.